Expansionary and contractionary technology improvements: conference paper - Balleer, Almut; Enders, Zeno (Jahrestagung des Vereins für Socialpolitik 2013, 2013)
This paper examines the effects of expansionary technology shocks (shocks that increase labor productivity and factor inputs) as opposed to contractionary technology shocks (shocks that increase labor productivity, but decrease factor inputs). We estimate these two shocks jointly based on a minimum set of identifying restrictions in a structural VAR. We show that most of the business cycle variation of key macroeconomic variables such as output and consumption is driven by expansionary technology shocks. However, contractionary technology shocks are important to understand the variation in labor productivity and production inputs. In addition, these shocks trigger different reactions of certain variables, which can help explain why existing evidence on technology shocks does not deliver clear results. In a simple DSGE model with managerial technology, which is consistent with our identifying restrictions, we interpret contractionary technology shocks as process innovations and motivate the difference to expansionary technology shocks.
Keywords: Graue Literatur; Konferenzschrift